دور قدرات المدرب المميز في تحسين أداء العاملين - بحث استطلاعي لاَراء عينة من الأفراد العاملين في المديرية العامة لتربية السليمانية - رسول, هوشمةند محمد; محمد, أمجد عبدالله; الدين, نيشتمان عثمان محي (Sulaimani Journal for Humanities, 2021)
The role of the trainer in the training process could be very effective if managed properly. In this regard, the study intends to identify the importance of the professional trainers’ capabilities in the training process. It also aims to identify approaches that helps organizations to take advantage of the trainer capacity in the performance of the employees’ competency specifically at General Directorate of Education in Sulaymaniyah. The quantitative research design was used through administering questionnaire. The sample size of 100 has been taken and 89 of them has been returned for the final analysis. The Statistical Package for Social Sciences (SPSS-21) has been used to analyse the data through Arithmetic means, Standard Deviations, Correlation Coefficients, and Simple Regression Coefficients. The study found a significant correlation between the capacity of the professional trainer and employees’ performance in education sector. The current study recommends that public sector institution in education sector should consider the role of competent and professional trainer in the development of employees’ performance in forms of capacity building, skills and competency development. Human capital investment plays a major role in the development of organizations; thus, prefrontal trainers could have major impact on the performance of employees through intensive and effective training process.
Keywords: trainer; coaching; capacity building; education sector; employees performance